An exploration on the habitat, feeds and distribution of Tarsius tarsier (tarsier) in Selayar Island and Patunuang Nature Reserve, South Sulawesi - WIRDATETI WIRDATETI; HADI DAHRUDIN (Biodiversitas Journal of Biological Diversity, 2008)
This research was conducted in the forest of Selayar Island and in the Nature Reserve on forest of Patunuang South Sulawesi. The study sites were located at 0-250 m above sea level on four locations. Data being collected were the distribution, type of feeds, nest sites, habitat utilization and of type. During the observation, we found at least 10 nest sites which were distributed on three locations. The tarsier consume mainly insect, and it isnâ€™t collected. Fifty two species from 31 families were identified being habitat and five species from three families were the nest of Tarsier which were dominated by bamboo.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Tarsius tarsier, feed, habitat, distribution, Selayar Island.